Gut bacteria and the host synergies promote resveratrol metabolism and induce tolerance in ALD mice - Song-xia Zhang; Fang-fang Hu; Huan Chen; Jing Guo; Zhong-wen Xiang; Xin Ding; Meng-ling Ye; Wen-li Ye; Jun-hong Chen; Xin Wang; Wen-jing Han; Hong-hao Zhou; et al. (npj Biofilms and Microbiomes)
Abstract Drug tolerance is clinically common but its mechanism is unclear. Previous studies found RSV tolerance in ALD treatment. This study explores mechanisms involving gut bacteria and host factors. Male C57BL/6J mice were induced into ALD with the Lieber-DeCarli alcohol diet, then ALD-RSV group mice were gavaged RSV (150 mg/kg/day) for 5 weeks. Throughout the experiment, ALD and ALD-RSV mice were on the Lieber-DeCarli alcohol diet, while the Vehicle group received a control diet. By week 5, tolerance to RSV efficacy emerged, with markedly reduced RSV exposure at the final dose. ALD-RSV group exhibited increased levels of Eggerthella lenta (E.lent), which metabolizes RSV into dihydroresveratrol (DHR). Chronic RSV treatment upregulated UGT1A1, the enzyme converting RSV into its primary metabolite, trans-resveratrol-3-O-β-D-glucuronide (R3G). The synergy between gut bacteria and host factors enhances RSV metabolism in ALD mice, driving tolerance and offering insights into other clinical drugs tolerance mechanisms.